Sub-micron features from polymer-derived SiOC via imprint lithography. Issue 4 (April 2019) - Gervasio, Michelle; Lu, Kathy
Abstract: Silicon oxycarbide (SiOC) is a unique class of materials with great potential for facile manufacturing of complex shaped high temperature parts and devices. In this study, we examine the characteristics of micron-sized ridge and rod patterns of SiOC created by imprint lithography. Feature fidelity, shape change, and shrinkage are studied as a function of pyrolysis condition and feature size. All the features have acceptable surface fidelity under the pyrolysis conditions studied. However, pronounced rounding and flattening of patterned features are observed as the pyrolysis temperature increases or the feature size decreases. Based on the Kelvin and Gibbs-Thomson equations, we can predict the feature evolution and show that the feature rounding and flattening are due to surface diffusion and evaporation-condensation. As a result, the features also have more linear shrinkage than the bulk.